Raziskovalna izhodišča besedilnofonetične analize slovenskega medijskega govora - Huber, Damjan (Slavistična revija, 2017)
Prosody, or sentence phonetics, is a relatively poorly researched area in Slovenian linguistics. This article presents a piece of prosodic research: an analysis of sentence stress from the perspective of text genre predictability, emphasizing the importance of specific research phases, particularly the selection of speakers, preparation, transcription and segmentation of material, and a two-stage confirmation of the research hypotheses using audio and computer analysis. The research is based on a corpus of selected Slovenian television discussion programs-in other words, on authentic and relatively spontaneous media speech.
Keywords: besedilna fonetika; besedne vrste; fonetika; medijski govor; phonetics; poudarek; Slovene; slovenščina